2018
DOI: 10.17645/si.v6i3.1477
|View full text |Cite
|
Sign up to set email alerts
|

‘Damn It, I Am a Miserable Eastern European in the Eyes of the Administrator’: EU Migrants’ Experiences with (Transnational) Social Security

Abstract: The European Union has given itself unique worldwide regulations so that EU citizens can port their social rights transnationally in case of migration. Yet this political and legal statement becomes flawed once a sociological perspective is adopted to look into the actual experiences of migrants. TRANSWEL (2015–2018), an ongoing international research project—applying a mixed-method approach to compare four country-pairs (Bulgaria-Germany, Estonia-Sweden, Hungary-Austria, Poland-UK)—has shown that mobile EU ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Our previous research (Holzinger, 2020;Scheibelhofer & Holzinger, 2018;Scheibelhofer et al, 2020) identified difficulties in handling linguistic diversity-both among AMS clients and within the institution itself-which are evident in the language barriers and pressure experienced by street-level bureaucrats (Lipsky, 1980). In a previous study (Holzinger, 2020) we included input from the AMS' migrant clients and will additionally focus on their perspective in a future research project (the FWF Austrian Science Fund-financed project "Investigating the Social Construction of Deskilling Among 'New' EU Migrants in Vienna").…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research (Holzinger, 2020;Scheibelhofer & Holzinger, 2018;Scheibelhofer et al, 2020) identified difficulties in handling linguistic diversity-both among AMS clients and within the institution itself-which are evident in the language barriers and pressure experienced by street-level bureaucrats (Lipsky, 1980). In a previous study (Holzinger, 2020) we included input from the AMS' migrant clients and will additionally focus on their perspective in a future research project (the FWF Austrian Science Fund-financed project "Investigating the Social Construction of Deskilling Among 'New' EU Migrants in Vienna").…”
Section: Methodsmentioning
confidence: 99%
“…In an increasingly mobile world, the organisation of social security faces new challenges (Sabates-Wheeler, Koettl, & Avato, 2011). Additionally, migrants within the EU-where a unique transnational social security system has been established-face substantial barriers when accessing welfare-related services and resources (Scheibelhofer & Holzinger, 2018;Seeleib-Kaiser & Pennings, 2018). For example, studies from Germany and Austria have shown that the enforcement of German as the language of administration and communication is the main informal barrier in this regard (Holzinger, 2020;Ratzmann, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the variation in welfare rights for immigrants is also due to the local implementation of policies, particularly the degree of discretionary powers conferred upon local actors and street level bureaucrats. Indeed, in addition to these restrictive eligibility criteria, immigrants face intangible obstacles, such as suspicion and fear, when trying to gain access to social services (Scheibelhofer and Holzinger 2018). Previous research has highlighted the importance of social workers in the lives of immigrants and the effects of power dynamics that may exist in these relationships (Bourgois and Schonberg 2009).…”
Section: Immigrant Eligibility Across Welfare Statesmentioning
confidence: 99%
“…An increasing number of empirical studies tackles these questions of street-level implementation and EU migrants’ access to social benefits (e.g. Carmel et al, 2016; Heindlmaier and Blauberger, 2017; Scheibelhofer and Holzinger, 2018).…”
Section: Social Policy Without a Mandatementioning
confidence: 99%
“…Another influence may affect the potency of transnational social rights related to social-security coordination. Empirical studies have shown that EU migrants’ entitlement and access to social rights is highly contingent upon national regulations on residency, welfare conditionality, high levels of discretion and complex bureaucratic requirements such as the Swedish PIN (Carmel et al, 2016; Scheibelhofer and Holzinger, 2018). The street-level interaction of supranational policies (that reward mobility) and national regulations (that reward sedentarism) further circumcises the already deficient transnational social rights.…”
Section: Social Citizenship Within the Eu: A Marshallian Reassessmentmentioning
confidence: 99%